Psychological Symptoms Among Healthcare Workers Handling COVID-19 Patients. - Sim, Sze Kiat; Lau, Bik Liang; Siti Rosnaini Zaila, Ramli; Nur Hazira, Abdul Muti; Nur Muzfirah Aniqah, Abdul Rahman; Jevitha Panicker, Balachandran; Alya Syafiqah, Hamzah (Malaysian Medical Association, 2021)
Introduction: Healthcare workers serve as the frontliners against the coronavirus 2019 disease (COVID-19) and this puts them most at risk of infection as they attend to numerous patients with unknown status. This study aimed to examine stress, anxiety, and depression among healthcare workers caring for COVID-19 patients in Sarawak General Hospital (SGH), Malaysia. Materials and Methods: This cross-sectional observational study conducted in SGH during the pandemic with an online self-administered questionnaire composed of two parts, the socio-demographic characteristics, and the Depression Anxiety Stress Scale (DASS). Results: A total of 105 healthcare workers responded to this study. A questionnaire in both Bahasa Melayu and English was used. The findings showed that all healthcare workers had mild anxiety, with the majority experiencing mild stress (57.1%), and almost half of the respondents experiencing mild depression (41%). Female subjects had a significant higher mean score in anxiety level and stress level compared to male subjects (10.0±3.20 vs. 8.6±2.93, p<0.05; 14.1±4.76 vs. 10.7±3.70, p<0.05, respectively). Staff who were transferred from other units to handle COVID-19 cases experienced more psychological symptoms. There were significant correlations between the depression, anxiety and stress levels among the healthcare workers and the number of children they had (r=0.739, p=0.001; r=0.642, p=0.001; r=1, p =0.001 respectively). However, the stress level among the healthcare workers was reversely correlated with their years of working experience (r=-0.199, p=0.042). Conclusion: This study identified some socio-demographic factors associated with increased levels of stress, anxiety and depression among the healthcare workers during pandemic, which may lay ground for future interventions.